Re-evaluation of the potential of South Muntenia region for the improvement of the rural development strategies - Elena Lascăr; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The integrated sustainable development strategy of South Muntenia Region presented within the work, constitutes a projection for the very immediate period, respectively year 2015, of the rural area development in a balanced manner and it is to be proposed to the authorities involved at regional level The South Muntenia Regional Development Board (1) and a county level (The County Councils) (2) in the implementation of the development policies. The strategy aims a wide range of economic, social and environment issues of the communities that are relevant in order to define the objectives needed to obtain the sustainable development and the increase of the economic and social cohesion in the region. Following the analysis of the funding programs for the rural area development projects, with social and economic impact, we found out that for South Muntenia Region, the rural development strategy must contain measures and indicators of the development at an integrated level, relating to the following constitutive elements : the area infrastructure development strategy, the strategy for SMEs development in South Muntenia Region, the strategy for environment protection in South Muntenia Region; the strategy and programs for the increase of nutritional level (qualitative and quantitative) of the rural population in South Muntenia Region.
Keywords: 330; strategy; analysis; program; rural; development